The digitalization of the humanitarian supply chain performance management literature and practice - Ester Lisnati Jayadi (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – This study aims to review the current research in the digitalization of the humanitarian supply chain performance management (HSCPM) and complement the insights found in the literature with the support of humanitarian organization (HO) reports. As a result, this study also identifies research gaps and directions for future research. Design/methodology/approach – The study first used a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis to collect and review 25 peer-reviewed articles. Second, the study complemented the articles’ findings by collecting and analyzing 12 HO reports. Findings – The study reveals the common understanding and links between HSCPM concepts and digitalization approaches, determining that the digitalization approaches per se used in the literature are indistinct and fragmented. Furthermore, it reveals the gaps between literature and practice that cause the research to develop slowly. Some suggestions are made to aid relevant future research. Both gaps and research directions are presented in Table 5. Research limitations/implications – This study first contributed to methodology in reviewing the digitalization of HSCPM research from literature and practical perspectives. There is a need to expand the data collection scope, integrate various analyses and foster collaborations with multi-disciplinary researchers and practitioners. Social implications – This study highlights the gaps and potential pathways for the research community to conduct future research investigations into the digitalization of HSCPM. Originality/value – To the best of the authors’ knowledge, this is one of the first studies to analyze the HSC’s current research into the application of digitalization in HSCPM from both academic and practical perspectives. It also provides a replicable methodology for future studies.